Kepuasan Seleksi dan Atribut Perguruan Tinggi: Mediasi Kepuasan Informasi: Selection Satisfaction and Attributes of Higher Education Institutions: Mediation of Information Satisfaction - Irfandi Buamonabot; Muhammad Asril Arilaha; Johan Fahri (Society, 2021)
This study aimed to examine the satisfaction of information availability in mediating the relationship between attributes of and satisfaction in choosing higher education institutions for Universitas Khairun and IAIN Ternate. A total of 252 students from both institutions were involved in this survey, with an effective rate of return of 70%. A hierarchical regression analysis was run by using IBM SPSS version 24. The results showed that for Universitas Khairun, information satisfaction fully mediates the relationship between attributes and satisfaction in choosing a university. In contrast, for IAIN Ternate, information satisfaction is only an independent variable. The implications and suggestions for further research are also discussed in this study.